Neuron specific enolase - selective marker for small-cell lung cancer - Ilievska Poposka, Biljana (Radiology and oncology (Ljubljana), 2004)
Background. Neuron specific enolase (NSE) is an isomer of the glycolytic enzyme enolase, which was first found in extracts of brain tissue, and was later shown to be present in neuroendocrine cells and neuroendocrine tumours. The aim of the study was to confirm the importance of serum NSE as a tumour marker in patients with small-cell lung cancer. Patierits and methods. Serum levels of NSE were measured by the radioimmunoassay in 71 patients with lung cancer (LC), in 24 patients with non malignant lung diseases and in 28 healthyadults. Results. According to the serum values in the group of healthy adults, 16.6 ng/ml was determined as a cut of level of NSE. By the specificityof 88.13% in the group of non malignant lung diseases, the sensitivity of 47.82% was obtained in patients with LC, which increased to 72.72% in the patients with SCLC. In patients with non-small-cell lung cancer (NSCLC) the sensitivity of NSE test was 38.89%. The patients with SCLC-extensive disease had a significantly higher mean NSE level (290.48 ng/ml) than patients with the limited stage disease (46.94 ng/ml). Serial measurements in 16 patients receiving combined chemotherapy and/or radiotherapy showed an excellent correlation between serum NSE level and clinical response. Conclusions. These results indicate that serum NSE may be auseful marker for diagnosis, staging and for monitoring response to the therapy in patients with SCLC.
Keywords: Blood; Carcinoma, Small Cell; diagnostika; Fosfopiruvatna hidrataza; Immunoassay; Imunski testi; Karcinom drobnocelični; Lung Neoplasms; Neoplasm Staging; Novotvorba, stadij; Občutljivost in specifičnost; Phosphopyruvate Hydratase; pljučne bolezni; Pljučne novotvorbe; rak (medicina); Sensitivity And Specificity; Tumor Markers, Biological; tumorski označevalci; Tumorski označevalci biološki